NUMERICAL SIMULATION OF Mw 8.3 SOUTH BURU FAULT TSUNAMIS WITH 3D SLIP EVOLUTION IN AMBON - Kelibulin, Josephus Ronny; Latumeten, Grimaldy Rooy; Elake, Alexander Yosep; Lebang, Annamaintin Kobong (Universitas Mataram, 2025)
This study investigates the tsunami hazard potential induced by the activity of the South Buru Thrust Fault on the coastal areas of Ambon City through two-dimensional (2D) numerical modelling using the COMCOT v1.7 software, while incorporating three-dimensional (3D) slip evolution from the fault scenario. The earthquake scenario was set at Mw 8.3 based on fault length, width, and slip potential estimates, representing an extreme seismic event in the region. By integrating 3D slip evolution into the 2D tsunami model, the approach accounts for spatial variations in vertical displacement along the fault plane, directly influencing tsunami generation and propagation. The simulation results show significant spatial variations in tsunami run-up heights and inundation zones, with maximum run-up recorded at Kapahaha (13.08 m, arrival time 832 s) and Slamet Riyadi Port (12.02 m, arrival time 786 s). In comparison, minimum values occurred in Ambon's northern and northeastern parts (<1 m). The affected area and inundation distance from the shoreline also vary, e.g., Kapahaha (12,813 m², 159 m) and Slamet Riyadi Port (414,158 m², 1,213 m). Areas experiencing the highest tsunami inundation are Latuhalat (>5 m), followed by Galala–Wayame–Laha (3–5 m) and Paso–Rumah Tiga–Hative Kecil (2–4 m). The distribution of tsunami waves is influenced by coastal morphology, wave direction, and the presence of bays and capes, which can either amplify or block waves. Further analysis highlights the effects of seafloor topography, coastal morphology, and wave propagation pathways on run-up heights and arrival times. These findings underscore the importance of considering multi-segment rupture models, 3D deformation, and coastal morphology in tsunami hazard assessments and contribute to more realistic, source-specific mitigation strategies in tectonically complex regions such as Ambon.